Computational Modelling, Synthesis and Biological Evaluation of Guanidinium-like Derivatives as Protein Kinase Inhibitors for the Treatment of Cancer - PREVITALI, VIOLA (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2018)
Kinases have emerged as one of the most intensively pursued targets in current medicinal chemistry research, and to date, the FDA has approved 31 small molecule kinase inhibitors (SMKI), with several therapeutic applications, particularly cancer. Previous studies in Rozas? group identified a guanidinium-based lead compound capable of inhibiting B-Raf (kinase frequently altered in the Ras/Raf/MEK/ERK pathway in cancer) through a hypothetic type-III allosteric mechanism. Previous and on-going molecular-modelling studies point towards the idea that this compound forms hydrogen-bond/electrostatic interactions with one of the ATP-phosphates through the mono-substituted guanidinium moiety, thus, positioning the lipophilic (4-Cl-3-CF3)-Ph group in a hydrophobic pocket of the enzyme. In this research, we have computationally studied the interactions established by this lead compound with (i) isolated ATP (through Density Functional Theory calculations) and (ii) an active phosphorylated ATP-containing B-Raf protein (through Molecular Dynamics simulations and docking), which represents the first model of this type of kinase containing ATP and hence suitable for structure-based design of type-III inhibitors of an active kinase. Moreover, 25 new aromatic derivatives have been synthesized to clearly identify the structural motifs that determine the allosteric inhibition of the Ras/Raf/MEK/ERK pathway and derive the corresponding structure-activity relationships. Several different biochemical assays were conducted to investigate their potential as anticancer agents and protein kinases? inhibitors. Firstly, their cytotoxic effect was assessed in promyelocytic leukaemia cells HL-60, and, for some chosen derivatives, also in breast cancer MCF-7, cervical HeLa, colorectal carcinoma HCT116 and HKH2 and multiple myeloma, H929 and U266B1 cell lines, to clearly establish their therapeutic profile. Secondly, flow-cytometry and western blotting studies were carried out to investigate the apoptosis-inducing activity of these derivatives. Their safety profile was established with assessment of their toxicity against non-tumorigenic epithelial MCF10A and human platelets and their ?druggability? estimated with computer-based prediction of their pharmacokinetics characteristics. The 3-amino-4?-guanidino phenoxypyridine 66 has distinguished itself among the other compounds for its exclusive high potency against a wide range of cancer cell lines, its ability to induce apoptosis and it low toxicity. Therefore, it now represents a new hit molecule towards the development of type-III allosteric inhibitors of the Ras/Raf/MEK/ERK pathway.
APPROVED
Keywords: Protein Kinase; Docking; Ras/Raf/MEK/ERK; Drug Discovery; Molecular Dynamic; Guanidine; Density Functional Theory; Synthesis